Development Of Digital Indonesian Rupiah Through Blockchain Technology - Lista Meria; Mariyanti, Tatik; Isabella Maria (Blockchain Frontier Technology, 2024)
In the current era of the fourth industrial revolution (Revolution 4.0), money plays a central role in various aspects of life, where all forms of goods and services require transactions involving currency. Money serves as a crucial element influencing economic dynamics and acts as a primary parameter in determining monetary policies across different nations. With time, the evolution of the economy, and the increasingly complex human behavior, the concept of money undergoes a significant transformation. It initially originated from barter systems, subsequently evolving into metal coins and paper currency as the official means of exchange to meet the necessities of life. This research focuses on the latest currency model introduced by Bank Indonesia, namely the digital rupiah based on blockchain technology. The study aims to explore the foundation for the government's establishment of digital currency and to elucidate whether conventional currency is presently adequate to fulfill human transaction needs. The research methodology employed is qualitative descriptive with a literature review approach, where the author endeavors to elaborate in detail on the digital rupiah. The research findings conclude that the government's introduction of the digital rupiah aims to provide a modern solution to the inefficiencies of the payment system and financial infrastructure. This digital currency also functions as a tool to directly monitor inflation rates and enables the implementation of monetary policies that can be directly experienced by the public.